Nanoemulsions as vehicles for transdermal delivery of aceclofenac - Shakeel, Faiyaz (Springer-Verlag, 2007)
The aim of the present study was to investigate the potential of a nanoemulsion formulation for transdermal delivery of aceclofenac. Various oil-in-water nanoemulsions were prepared by the spontaneous emulsification method. The nanoemulsion area was identified by constructing pseudoternary phase diagrams. The prepared nanoemulsions were subjected to different thermodynamic stability tests. The nanoemulsion formulations that passed thermodynamic stability tests were characterized for viscosity, droplet size, transmission electron microscopy, and refractive index. Transdermal permeation of aceclofenac through rat abdominal skin was determined by Franz diffusion cell. The in vitro skin permeation profile of optimized formulations was compared with that of aceclofenac conventional gel and nanoemulsion gel. A significant increase in permeability parameters such as steady-state flux (J(ss)), permeability coefficient (K(p)), and enhancement ratio (E(r)) was observed in optimized nanoemulsion formulation F1, which consisted of 2% wt/wt of aceclofenac, 10% wt/wt of Labrafil®, 5% wt/wt of Triacetin®, 35.33% wt/wt of Tween 80®, 17.66% wt/wt of Transcutol P®, and 32% wt/wt of distilled water. The anti-inflammatory effects of formulation F1 showed a significant increase (P<.05) in percent inhibition value after 24 hours when compared with aceclofenac conventional gel and nanoemulsion gel on carrageenan-induced paw edema in rats. These results suggested that nanoemulsions are potential vehicles for improved transdermal delivery of aceclofenac.